Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/aenm.201700835
|View full text |Cite
|
Sign up to set email alerts
|

The Space Confinement Approach Using Hollow Graphitic Spheres to Unveil Activity and Stability of Pt‐Co Nanocatalysts for PEMFC

Abstract: The performance of polymer electrolyte fuel cells is strongly correlated to the electrocatalytic activity and stability. In particular, the latter is the result of an interplay between different degradation mechanisms. The essential high stability, demanded for real applications, requires the synthesis of advanced electrocatalysts that withstand the harsh operation conditions. In the first part of this study, the synthesis of oxygen reduction electrocatalysts consisting of Pt-Co (i.e., Pt5Co, Pt3Co, and PtCo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…The adoption of advanced catalyst supports with high conductivity, sufficient corrosion resistance and strong chemical interactions can offer an additional degree of freedom to tune the ORR catalysts . The electrocatalysts can be supported on various carbon materials such as carbon black, hollow graphitic spheres (HGS), carbon nanotubes (CNTs) and reduced graphene oxide (rGO) or its functional derivatives as well as noncarbonaceous materials . Selective carbon or noncarbon supports can introduce synergistic catalytic effect between nanocatalysts and the supporting substrate.…”
Section: Nanoscale Structure Design For High‐performance Pt‐based Orrmentioning
confidence: 99%
“…The adoption of advanced catalyst supports with high conductivity, sufficient corrosion resistance and strong chemical interactions can offer an additional degree of freedom to tune the ORR catalysts . The electrocatalysts can be supported on various carbon materials such as carbon black, hollow graphitic spheres (HGS), carbon nanotubes (CNTs) and reduced graphene oxide (rGO) or its functional derivatives as well as noncarbonaceous materials . Selective carbon or noncarbon supports can introduce synergistic catalytic effect between nanocatalysts and the supporting substrate.…”
Section: Nanoscale Structure Design For High‐performance Pt‐based Orrmentioning
confidence: 99%
“…Owing to the easy‐to‐manipulate microstructure and delimited local voids, researchers recently have demonstrated that elaborated hollow nano/microstructures exhibit superior performance as the primary materials in a variety of emerging research fields, such as catalysis, lithium‐ion batteries (LIBs), supercapacitors, proton‐exchange‐membrane fuel cells (PEMFCs), chemical sensors, and biomedicine . Along with tremendous progress on microstructural characterizations and basic growth mechanism of nanocrystals, hollow nanomaterials become one of the hot spots in the modern research of nanoscience, particularly focusing on the development of synthetic methodologies and structure‐correlated properties …”
Section: Introductionmentioning
confidence: 99%
“…and enrich the functions (e.g., magnetic separation, stimuli‐responsive, tandem catalysis, etc. ), several functionalization synthetic methods have been applied to upgrade simplex hollow building blocks to complex hierarchical structures: ship‐in‐a‐bottle methods are applied for the synthesis of encapsulated hollow structures to disperse and stabilize the catalytic sites; multistep template methods are used for the synthesis of multishelled hollow structures to increase the number of active sites; pyrolysis of metal–organic polymers for single atom site hollow structures maximizes the exposure of metal atoms to promote the overall activity; surface molecular modification of hybrid hollow structures at diverse spatial sites enables the catalysis of tandem reactions on the integrated multiple reaction sites …”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23] In a series of papers, Mayrhofer and co-workers showed that during potential cycling with UPL higher than 1.1 V, greater Pt dissolution occurs during the cathodic scan than during the anodic scan. 17,21,22 The amount of Pt dissolved during the cathodic scan increased with increasing UPL as well as with decreasing scan rate and occurred at potentials below 1 V in the cathodic scan.…”
mentioning
confidence: 99%